Body Image and Other Mood Vulnerabilities in Adolescents with Polycystic Ovary Syndrome and Metabolic Alterations - Federica Barbagallo; Lara Tiranini; Chiara Placentino; Giacomo Mariacci; Manuela Piccinino; Laura Cucinella; Aldo E. Calogero; Rossella E. Nappi (MDPI AG, 2024)
Introduction: Psychological vulnerability is a relevant component of polycystic ovarian syndrome (PCOS), but it is still under-explored, especially during adolescence. The aim of this study was to describe a selection of psychometric characteristics in a clinical sample of Italian adolescents with PCOS. Moreover, we reported the associations of body image, eating attitudes, and mood with metabolic features. Methods: Our sample included 128 adolescent girls (age range: 14-19 years) with PCOS. Validated psychometric questionnaires were administered: State Anxiety Inventory (STAI), Beck Depression Inventory (BDI), Body Attitude Test (BAT), Bulimia Investigation Test (BITE), Eating Attitudes Test (EAT), and Perceived Stress Scale (PSS). Results: Anxiety was the most prevalent mood disorder (63.1% trait anxiety and 57% state anxiety). Our cohort also showed a high prevalence of depression (39.1%), body image dissatisfaction (49.2%), disordered eating (11.7%), and bulimic risk (41.4%). PCOS adolescents with obesity and insulin resistance (IR) had statistically significant higher body image distress compared to those with normal weight and without IR (p < 0.001). The Sobel test for mediation showed that body image dissatisfaction mediates the relationship between state anxiety and bulimic risk (Z = 3.42, p < 0.001) and between depression and bulimic risk (Z = 4.59, p < 0.001). Conclusions: A considerable number of patients with PCOS experience psychological disorders during adolescence. IR and obesity play a role in the distress associated with body image, further contributing to psychological vulnerability, especially in the bulimic domain. A comprehensive biopsychosocial approach in adolescents with PCOS represents the basis for effectively managing and preventing complications arising from both psychological and biological disorders in adulthood.